The effect of fertilization on productivity and grain quality of different varieties of triticale - Lalević, Dragana N; Biberdžić, Milan O; Ilić, Zoran S; Milenković, Lidija R; Stojiljković, Jelena V (Journal of Agricultural Sciences (Belgrade), 2019)
This paper presents the influence of variety and different doses of applied nitrogen on grain yield and protein content of triticale. The experiment was set in the period from 2010-2012 in the north of Montenegro, in the vicinity of Bijelo Polje. The research included 5 varieties of winter triticale (Odyssey, Kg-20, Triumph, Rtanj and Tango) and the following varieties of fertilization: control (without fertilization), only nitrogen in the amount of 60 kg ha-1 and nitrogen in the amount of 60 and 90 kg ha-1 in combination with the same amount of phosphorus and potassium (80 kg ha-1). The results of the study showed that the lowest average grain yield was obtained on the non-fertilizing variant - control. The use of fertilizers in all tested varieties has led to a very significant increase in yield on all variants compared to control.  Kg-20 variety had the lowest average yield, and variety Tango had the highest. The highest average protein content was achieved on the fertilizer variant where only nitrogen was used in the amount of 60 kg ha-1. Among the researched varieties, variety Triumph had the highest protein content in the grains. The data on the achieved yields and the content of protein in grains, depending on the variety and the used doses of fertilizer, indicate the characteristics of certain varieties and can serve as a criteria for the selection of the most suitable cultivar variety. This is particularly important for cattle-oriented farms, where the main priority is to ensure a sufficient amount of quality food. Key words: yield, protein content, genotype, nitrogen, phosphorus, potassium.